Sammy feels shy - Percival, Tom, 1977- (Percival, Tom, 1977- Big bright feelings., 2025)
Sammy LOVES having fun. Especially at home. But in big groups -- like at school, birthday parties, even the ice cream truck-he doesn't love feeling like other people are looking at him, and it's really hard talking to other people. Everyone tells Sammy not to be so shy. But one day, it gets so hard and scary that he starts to turn pink, and then pinker...until he's bright pink ALL OVER! Then he doesn't want to see anyone or do anything. But hiding out -- alone -- isn't very fun. Can Sammy learn how to tackle his fears --and go back to his usual color? This warm, affectionate, and relatable book is the perfect starting place for talking to children about shyness and feeling self-conscious.